Tourist analysis based on strengths and intrinsic weaknesses of the territory - Sánchez Cuenca, Luis Miguel (2020)
This study focuses on five parishes in the Zaruma canton, with the aim of determining the main strengths or weaknesses that promote or hinder tourism in the sector. The analysis is based on the guidelines of the Methodological Guide for the ranking of attractions and generation of tourist spaces in Ecuador. The first stage was used with its two initial phases, and to facilitate the analysis of the criteria, a weighted percentage was applied to the evaluation criteria, in order to make statistical graphs of the attractions, which allowed us to identify that the tourism potential lies in the cultural-heritage tourism modality and that its complementary attractions, despite having many weaknesses, can be developed with proper management.